2023
DOI: 10.1021/acs.biochem.3c00084
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Photoreaction of a Retinal Photoisomerase, Retinal G-Protein-Coupled Receptor RGR

Abstract: Retinal G-protein-coupled receptor (RGR) plays a crucial role in the visual system of vertebrates as a retinal photoisomerase, which isomerizes all-trans-retinal to 11-cis-retinal to maintain the photosensitivity of visual rhodopsins. Despite the previous characterization of bovine RGR, little is known about the spectral properties of RGR from other species. In addition, photoreactivity of the 11-cis-retinal-binding form remains unclear. In this study, we revealed that human and chicken RGRs form blue-absorbin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…These observations overall indicate RGR to be a monostable nonvisual opsin with trans-cis photoisomerization activity. Recent studies have suggested the bistability of RGR ( 32 ), which is a plausible interpretation under the conditions used (RGR in detergent micelles). Considering our findings that the hydrolysis of the 11- cis -retinylidene adduct is much slower in RGR immunopurified in detergent micelles as compared to native microsomal membranes, the delayed hydrolysis rate in detergent would allow time for another photoisomerization event, thereby conferring an apparent bistable nature.…”
Section: Discussionmentioning
confidence: 92%
“…These observations overall indicate RGR to be a monostable nonvisual opsin with trans-cis photoisomerization activity. Recent studies have suggested the bistability of RGR ( 32 ), which is a plausible interpretation under the conditions used (RGR in detergent micelles). Considering our findings that the hydrolysis of the 11- cis -retinylidene adduct is much slower in RGR immunopurified in detergent micelles as compared to native microsomal membranes, the delayed hydrolysis rate in detergent would allow time for another photoisomerization event, thereby conferring an apparent bistable nature.…”
Section: Discussionmentioning
confidence: 92%
“… 10 However, a more recent study estimated that photic RGR activity in a native membrane environment, in the presence of CRALBP, far exceeds the rate of 11- cis -retinol formation by the RPE in the dark. 9 RGR has been understood to be a bistable opsin 34 ; however, the extent to which RGR behaves as a bleaching opsin to release of 11- cis -retinal and support visual pigment recycling has not been thoroughly characterized. Here, we demonstrate the bleaching properties of RGR, measuring the rate of hydrolysis of the RGR* to quickly generate 11- cis -retinal.…”
Section: Discussionmentioning
confidence: 99%
“…[ 121,127 ] RGR resides in the RPE and Müller glia, where it binds all‐ trans ‐retinal to form a pigment that involves a photochemistry that is the reverse of that of the photoreceptor opsins, producing 11‐ cis ‐retinylidene that is hydrolyzed to generate 11‐ cis ‐retinal. [ 121,128,129 ] As a mono‐stable opsin, the rate at which RGR hydrolyzes its 11‐ cis product to resupply photoreceptors with 11‐ cis ‐retinal is not known. [ 121 ] Notably, the rate at which opsins consume 11‐ cis ‐retinal in the photoreceptors under daylight conditions is much faster than the rate at which the classical visual cycle generates 11‐ cis ‐retinal through RPE65, as demonstrated by the slow rate of dark adaptation.…”
Section: Mono‐stable Vs Bistable Opsinsmentioning
confidence: 99%